Dinamika Pembentukan Karakter Anak Melalui Aktivitas Berkuda Dan Memanah : Studi Kasus Di Pusat Riadah Wadiannour - Nabila Ayu Maharani; Mavianti Mavianti (Universitas Cokroaminoto Yogyakarta, 2025)
Character building in children is very important to form a good personality so that when they grow up they become individuals who are noble and able to provide benefits to others and the surrounding environment. This study aims to determine the dynamics of children's character building through horse riding and archery activities at the Wadiannour Riadah Center. This research uses a qualitative approach with a case study method. Data were collected through participatory observation, interviews, and documentation. The results showed that equestrian and archery activities at Pusat Riadah Wadiannour contribute positively to character education by proving that structured physical activities can shape children's positive character or behavior, especially in the aspects of discipline, responsibility, school motivation, improving focus and concentration, and orderliness or neatness.